The Onset and Progression of Hippocampal Synaptic Plasticity Deficits in the Q175FDN Mouse Model of Huntington Disease - Quirion, Jade G.; Parsons, Matthew P. (Frontiers in Cellular Neuroscience, 2019)
Huntington disease (HD) is an inherited neurodegenerative disease characterized by a clinical triad of motor, psychiatric and cognitive symptoms. HD is caused by a CAG repeat expansion in the gene encoding the huntingtin protein. Homozygosity for the HD-causing mutation is extremely rare; thus, the majority of HD patients express the mutant huntingtin protein in addition to reduced levels of the non-pathogenic huntingtin protein. Deficits in synaptic plasticity, including hippocampal long-term potentiation (LTP), have been identified in various mouse models of HD and are thought to contribute to the debilitating cognitive symptoms associated with the disease. However, the bulk of these studies used N-terminal fragment or homozygous knock-in mouse models of HD at symptomatic ages, and our understanding of the onset and progression of synaptic plasticity deficits in the HD brain is lacking. To better understand the time-course of synaptic plasticity deficits in HD, as well as the impact of heterozygous and homozygous huntingtin mutations, we quantified basal synaptic connectivity, presynaptic release probability, presynaptically-mediated post-tetanic potentiation (PTP) and postsynaptically-mediated LTP at presymptomatic, early symptomatic and late symptomatic ages in heterozygous and homozygous Q175FDN knock-in HD mice. Our results demonstrate clear age-dependent effects of the HD-causing mutation on both short and long-term plasticity that generally emerge earlier in homozygous mice. Interestingly, deficits in presynaptic short-term plasticity were more closely linked to disease progression than deficits in postsynaptic long-term potentiation, and heterozygous mice were more susceptible to an LTP deficit when induced by high frequency stimulation compared to theta burst stimulation. To the best of our knowledge, the present study represents the most thorough characterization to date of the onset and progression of hippocampal synaptic plasticity deficits in a mouse model of HD, and should prove valuable to future studies exploring cellular mechanisms underlying the debilitating cognitive decline in HD.